2017
DOI: 10.1038/s41598-017-14637-w
|View full text |Cite
|
Sign up to set email alerts
|

Two novel diterpenoid heterodimers, Bisebracteolasins A and B, from Euphorbia ebracteolata Hayata, and the cancer chemotherapeutic potential of Bisebracteolasin A

Abstract: Rare ent-abietane-rosane diterpenoid heterodimers, Bisebracteolasins A and B (1 and 2, respectively), were isolated from the roots of Euphorbia ebracteolata Hayata. Their structures and absolute configurations were elucidated from spectroscopic data and X-ray diffraction analysis. Compounds 1 and 2 exhibited moderate cytotoxic effects against five cancer cell lines. Compound 1 showed more effective antiproliferative activities against human tumour cells, HL-60 and SMMC-7721, with IC50 values of 2.61 and 4.08 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…These results indicated that TDEE was the anti-ascites active fraction of EER. Previous studies have shown that the diterpenoids from EER have inhibitory activities on tumor cells in vitro [ 5 , 23 ]. However, this study found that they have no effects on the tumor cell viability, cell cycle, or apoptosis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that TDEE was the anti-ascites active fraction of EER. Previous studies have shown that the diterpenoids from EER have inhibitory activities on tumor cells in vitro [ 5 , 23 ]. However, this study found that they have no effects on the tumor cell viability, cell cycle, or apoptosis of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Then, 204b could be transformed to 204c and 205a through the oxidation, further reaction with co-isolated ent -abietane 204d led to the production of 204 and 205 , respectively (Scheme 17). 125…”
Section: Biosynthesis Of Bisditerpenoidsmentioning
confidence: 99%
“…The genus Euphorbia is the largest in the Euphorbiaceae family, comprising more than 2000 species. Diterpenoids occurring in plants of the genus Euphorbia are considered to be their important taxonomic markers. , At present, eight diterpenoid dimers but none of the [4 + 2] type have been isolated from this genus. In our previous research, ten new abietane-type diterpenoid derivatives, including five meroditerpenoids with significant cytotoxicities, were isolated from the roots of Euphorbia fischeriana . These results greatly inspired our interests to discover for more structurally unique scaffolds from the title plant. As a result, one novel diterpenoid dimer named fischdiabietane A ( 1 ) was isolated and characterized, which possesses an unprecedented 6/6/6/5/7/6/6/6/6 fused nonacyclic carbon skeleton containing as many as 12 chiral centers (Figure ).…”
Section: Introductionmentioning
confidence: 99%